EVALUASI HASIL PROGRAM SIMPAN PINJAM KOPERASI SERBA USAHA DESA KOTA INDONESIA DALAM MENDUKUNG PROGRAM DAKWAH DI MA’HAD AL-ZAYTUN - Santoso, Bambang; Satria, Alfi; Sobirin (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to evaluate the results of the savings and loan program of KSU Desa Kota Indonesia in supporting the da’wah program at Ma’had Al-Zaytun, and to identify the supporting and inhibiting factors of the savings and loan program at KSU Desa Kota Indonesia in Ma’had Al-Zaytun. This research uses a descriptive qualitative method with a naturalistic qualitative approach. The data sources include primary data from the management of KSU Desa Kota Indonesia, and secondary data which consists of cooperative documents such as journals, KSU profiles, the KSU Desa Kota Indonesia business license, and others. Based on observations in several savings and loan cooperatives in Gantar, Wanguk, and Haurgeulis, the author selected KSU Desa Kota Indonesia as the research object due to differences in management related to the evaluation of the savings and loan program at Koperasi Serba Usaha Desa Kota Indonesia in supporting the da’wah program at Ma’had Al-Zaytun, Faculty of Syariah. The evaluation of the savings and loan program of Koperasi Serba Usaha Desa Kota Indonesia in supporting da’wah at Ma’had Al-Zaytun shows positive impacts, namely: 1) Economic improvement of members that supports da’wah activities, 2) Empowerment of members in financial management, 3) Increased community participation in da’wah, and 4) Program sustainability that depends on management and support from related parties. Overall, this cooperative plays a significant role in supporting da’wah through economic strengthening and community empowerment. Koperasi Serba Usaha Desa Kota Indonesia has played an important role in supporting the da’wah program at Ma’had Al-Zaytun through economic strengthening and community empowerment. Keywords: Program evaluation, KSU Desa Kota Indonesia;